2012
DOI: 10.1016/j.jvs.2011.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic liver masquerading as a floating intracaval mass

Abstract: Ectopic liver is defined as liver parenchyma situated outside the liver proper with no connection to native hepatic tissue. This rare developmental anomaly is most commonly described as an attachment to the gallbladder with an incidence <0.3%, but it has been reported in other locations within the abdomen and thorax.(2-4) Most cases are found incidentally in asymptomatic patients, but ectopic liver has been known to cause visceral or vascular obstruction.(4,5) Herein we present a unique case of ectopic liver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Although, the most common localization of ELT is gallbladder, it is seen both in intraabdominal and intra thoracic cavity. It was found in spleen, umbilicus, vena cava, and also in heart and lung [9–12] . Hepatobiliary system originates from foregut in the fourth week during embryological period.…”
Section: Discussionmentioning
confidence: 97%
“…Although, the most common localization of ELT is gallbladder, it is seen both in intraabdominal and intra thoracic cavity. It was found in spleen, umbilicus, vena cava, and also in heart and lung [9–12] . Hepatobiliary system originates from foregut in the fourth week during embryological period.…”
Section: Discussionmentioning
confidence: 97%
“…From intra abdominal sites the most frequent site where are found the majority of ectopic livers is the gallbladder (Tejada & Danielson;Arakawa et al;Sakarya et al, 2002;Acar et al, 2002;Catani et al, 2011;Martinez et al;Bal et al, 2015;Yahya et al, 2016;Karaca et al, 2016). Occasionally ectopic liver have been found in other organs like stomach (Huang et al, 2015, Barazza et al, 2016, in the upper pole of the spleen (Zonca et al, 2013), in the ligamentum hepato-umbilicalis (Lara-Díaz et al, 2011;Vaideeswar et al, 2011;Zonca et al), in the pancreas , kidney (Merve & Scheimberg 2014), left adrenal gland (Hashimoto et al, 1997) or have been found as intracaval floating mass (Morris et al, 2012;Rafiei et al, 2012). From the review of the literature a few cases of ectopic liver have been reported in the walls of stomach as submucosal tumors (Huang et al) or attached to serosa of stomach (Barazza et al).…”
Section: Case Reportmentioning
confidence: 99%
“…Accessory livers may have their own mesentery and, depending on their location, can drain into the biliary system or have no drainage system. Liver tissue connected with the main organ via a vascularized stalk may rarely have an unusual position, e.g., being situated within the suprahepatic part of the inferior vena cava, as a floating intraluminal polypoid mass (Morris et al 2012). An accessory liver lobe can be found in exomphalos/omphalocele (Tan and Tan 1971;Pereira et al 2005).…”
Section: Ectopic Liver: Anatomic Sites and Morphologymentioning
confidence: 99%